Analysis of Factors Affecting the Contamination of Entamoeba sp. cyst and Soil-Transmitted Helminths egg on Dug Well Water - Iza Billa Fahmi; Erma Sulistyaningsih; Dion Krismashogi Darmawan (Faculty of Medicine, University of Jember, 2021)
Dug well water is often polluted by fecal waste containment such as septic tank and pit latrine system due to its distance. The common pathogenic parasites found in fecal waste containment are E. histolytica and Soil-Transmitted Helminths (STH). The port de entry of both parasites is ingestion of contaminated food or water by fecal materials. This study was aimed to analyze factors affecting the existence of Entamoeba sp. cyst and STH egg on dug well water in Bungatan Village, Situbondo. This observational analytic study used cross-sectional approach, carried out 30 respondents in Bungatan Village, Situbondo. Entamoeba sp. cyst and STH egg were examined using sedimentation method, the distance of fecal waste containment to dug well measured by measuring tape. The characteristic of fecal waste containment and dug well was observed using questionnaires. The results showed 100% fecal containment used pit latrine system, 100% had an incomplete well standard, 66,7% had unstandardized distance with fecal waste containment. Entamoeba sp. cyst and STH egg were not found on all water samples. The soil condition near the dug well (acidity, temperature, moisture, and sunlight intensity) and physical condition (temperature) of dug well water were inappropriate to the development of Entamoeba sp. cyst and STH egg. The dug well's component and its distance to fecal containment did not affect Entamoeba sp. cyst and STH egg existence in all dug well water. The physical soil condition near the dug well and the temperature of dug well water were inappropriate to the development of both parasites. Keywords: Entamoeba sp., Soil Transmitted Helminths, Dug Well, Fecal Waste Containment